Exploring the Conundrum of Law Enforcement versus Personal Dignity: Constitutional Court Judges' Dissenting Opinions in Indonesia - Khadafi, Rizal; Abdi, Nurul Satria (JURNAL TRIAS POLITIKA, 2026)
The Republic of Indonesia's Constitutional Court (MK RI) garnered significant public attention during the 2024 elections due to two contentious rulings it rendered. The age restriction for presidential and vicepresidential candidates was the subject of the first ruling, while challenges to the election results were the subject of the second. It's interesting to note that a number of judges have expressed opinions that differ from the rulings in these two contentious decisions, a fact known as dissenting opinions. This study intends to investigate the legal foundation of dissenting opinions and the legal ramifications of such decisions using qualitative approaches, bolstered by document analysis, case studies, and jurisprudence analysis. This study concludes that, with regard to two contentious rulings made by the Constitutional Court of the Republic of Indonesia regarding the 2024 elections, divergent viewpoints have no bearing on the rule of law but do have an effect on judges' individual authority and can provoke public discussion. The contrasting viewpoints expressed in dissenting opinions contribute to a richer legal discourse, particularly when it comes to the significance of substantive and procedural justice in Indonesian elections. This study recommends that the nomination, determination, and selection of judges for the constitutional court be carried out in a transparent, responsible manner that takes into account increased public involvement in an effort to preserve legal sovereignty while defending the ideals and principles of democracy. Rather than going via a political process rife with interests that diminish the court's authority and credibility as a stand-alone judicial body